SID-2 is a conserved extracellular vesicle protein that is not associated with environmental RNAi in parasitic nematodes - Frances Blow; Kate Jeffrey; Franklin Wang-Ngai Chow; Inna A. Nikonorova; Maureen M. Barr; Atlanta G. Cook; Bram Prevo; Dhanya K. Cheerambathur; Amy H. Buck (Open Biology)
In the free-living nematode Caenorhabditis elegans, the transmembrane protein SID-2 imports double-stranded RNA into intestinal cells to trigger systemic RNA interference (RNAi), allowing organisms to sense and respond to environmental cues such as the presence of pathogens. This process, known as environmental RNAi, has not been observed in the most closely related parasites that are also within clade V. Previous sequence-based searches failed to identify sid-2 orthologues in available clade V parasite genomes. In this study, we identified sid-2 orthologues in these parasites using genome synteny and protein structure-based comparison, following identification of a SID-2 orthologue in extracellular vesicles from the murine intestinal parasitic nematode Heligmosomoides bakeri. Expression of GFP-tagged H. bakeri SID-2 in C. elegans showed similar localization to the intestinal apical membrane as seen for GFP-tagged C. elegans SID-2, and further showed mobility in intestinal cells in vesicle-like structures. We tested the capacity of H. bakeri SID-2 to functionally complement environmental RNAi in a C. elegans SID-2 null mutant and show that H. bakeri SID-2 does not rescue the phenotype in this context. Our work identifies SID-2 as a highly abundant EV protein whose ancestral function may be unrelated to environmental RNAi, and rather highlights an association with extracellular vesicles in nematodes.